Deformation Mechanisms Operating during Plastic Flow of An Az63 Magnesium Alloy Studied by the Stress Relaxation Technique - Trojanova, Zuzanka; Lukac, Pavel (Communications - Scientific letters of the University of Zilina, 2010)
Magnesium alloy AZ63 (Mg−6Al−3Zn) was deformed at temperatures between room temperature and 300 °C. Stress relaxation tests were performed in order to reveal features of the thermally activated dislocation mechanism. Internal and effective components of the applied stress were estimated. Very high values of the internal stress estimated at lower temperatures decrease rapidly with increasing deformation temperature. The apparent activation volume decreases with increasing effective stress. The values of the activation volume as well as the activation enthalpy indicate that the main thermally activated process is most probably the glide of dislocations in non−compact planes. Nonmonotonous temperature dependence of the flow stress was observed. Post relaxation effect was detected. Strain ageing effects are explained by the dynamic solute-dislocation interaction.